2022
DOI: 10.26603/001c.38043
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Guidelines for Use Following a Periacetabular Osteotomy (PAO): A North American Based Delphi Consensus

Abstract: Background Treatment of acetabular dysplasia with a periacetabular osteotomy (PAO) has been shown to improve long term outcomes and is considered the gold standard in the setting of symptomatic hip dysplasia in patients younger than 35 years of age. Post-operative rehabilitation following a PAO plays an important role in helping patients return to their prior level of function and reduce the impact of strength deficits that may persist. Currently, there is a paucity of research supporting post-operative rehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Questions ranged from speci c physical therapists to work with postoperatively, rehabilitation supplies such as walkers and other durable medical equipment, to different stretches and exercises that helped other patients' recovery and symptoms. Prior studies have shown the standardization of rehabilitative care following PAO is essential for achieving optimal outcomes despite other factors such as geographical location and socioeconomic status 5 . Connecting with physical therapists that specialize in PAO or developmental dysplasia of the hip (DDH) rehabilitation through use of social media or virtually could be a great opportunity for improving outcomes and marketing physical therapy services.…”
Section: Discussionmentioning
confidence: 99%
“…Questions ranged from speci c physical therapists to work with postoperatively, rehabilitation supplies such as walkers and other durable medical equipment, to different stretches and exercises that helped other patients' recovery and symptoms. Prior studies have shown the standardization of rehabilitative care following PAO is essential for achieving optimal outcomes despite other factors such as geographical location and socioeconomic status 5 . Connecting with physical therapists that specialize in PAO or developmental dysplasia of the hip (DDH) rehabilitation through use of social media or virtually could be a great opportunity for improving outcomes and marketing physical therapy services.…”
Section: Discussionmentioning
confidence: 99%
“…This study utilized a modified Delphi technique to establish group consensus on use of functional performance tests for individuals with non-arthritic intra-articular hip pain. 25,26 Methods for the current study are similar to those described in Disantis et al 27 Briefly, a list of relevant questions regarding the use of functional performance tests was determined and consensus was reached over three survey rounds. During round one, panelists were presented with list of potential topics via email.…”
Section: Methodsmentioning
confidence: 99%
“…Physical therapy plays an important role in postoperative care and recovery of hip preservation surgery 67 . Although a PAO is often combined with hip arthroscopy, the addition of hip arthroscopy does not dramatically change the rehabilitation.…”
Section: Clinical Scenariomentioning
confidence: 99%